Chapter 28: Geopolitical challenges of renewable energy adoption in MENA - Hatipoglu, Emre (Edward Elgar Publishing, 2023)
Will the energy transition perturbate geopolitics in the Middle East and North Africa (MENA)? Our answer is yes, and that answer rests on three observations. First, the region is cognizant of the threats that climate change poses to human security. Second, a global energy transition will increase the premium on low-cost and low-carbon-footprint oil in the MENA, especially for countries in the Gulf Cooperation Council; hence, the rising opportunity cost of consuming oil at home. In tandem, the energy transition constitutes an attractive area of investment for countries seeking to diversify their economic base. The resulting interest in renewable energy has the potential to create geopolitical challenges in border territories and exclusive economic zones and raises challenges for the regional governance of electricity trade and the global trade in renewables equipment. We also argue that renewables may play an important role in post-conflict recovery in many parts of the MENA.